Edukasi dan Penatalaksanaan Fisioterapi pada Kondisi Low Back Pain Myogenic dengan Infra Red dan Myofascial Release - Haryanti, Ajeng; Ramadhani, Alinda Nur; Kuswidyadhana, Naufal Ammar; Ahmadi, Rian Ghalib; Sukma, Tyan Antika (Prosiding University Research Colloquium, 2023)
Low Back Pain Miogenik is a lower back pain caused by muscle tension, Symptoms that occur in the lower back area such as pain and related to disorders of the musculoskeletal system. Excessive use of the spine causes functional ability disturbed. Methods: The method used in this program is the educational method and the provision of intervention wit infrared and myofascial release. Result: Based on the results of low back pain myogenic counseling and the provision of infrared and myofascial release modalities, it can be concluded that this activity has succeeded in educating the residents of Gulon village RT 02 RW 21 Jebres, Surakarta which can be assessed from the posttest questionnaire regarding myogenic low back pain.